ANALYSIS AND DESIGN OF DRAINAGE SYSTEM PLANNING STUDY (CASE STUDY GRAHA WISATA SIDOARJO RESIDENTIAL) - M. Fachrul Reza; Diah Ayu Restuti Wulandari (NAROTAMA UNIVERSITY, 2019)
Graha Wisata Sidoarjo Housing has a land area of 470,000 m2 located in Lebo Village, Sidoarjo District, Sidoarjo Regency. The housing is passed by the Anak Afvoer Sidokare channel. With the change in land function, it is necessary to analyze the capacity of the Anak Afvoer Sidokare watershed. The rainfall data used is the annual maximum rainfall from the rain station Durungbedug, Ketintang, Sidoarjo, Sumput .. The method of rainfall analysis uses the Log Pearson type III method. Planned flood discharge in the Anak Afvoer Sidokare watershed at 25 years using the Nakayasu method is 450.55 m3 / sec while the existing Afvoer capacity with dimensions of 10 m x 4.172 m is 537.39 m3 / sec, the cross section of the Son Afvoer Sidokare channel is not overflow.